Integrative Approach to Enhancing Linguists’ Background Knowledge in Culture and Art - Mukhametshina, Evelina Erkinovna; Solovyova, Elena Gennadievna; Pomortseva, Nadezhda Pavlovna (Journal of History Culture and Art Research, 2017)
In the conditions of the global cultural and educational space development, the humanity enjoys such ongoing processes as integration of knowledge, mutual influence and interaction of cultural traditions. Here the role of a translator/ interpreter as an ambassador of culture is growing; he/she is seen as a mediator between communicants belonging to different cultures with incompatible linguistic and conceptual pictures of the world. In this context, the translator’s background knowledge in various spheres plays a special role. The search for effective ways of enhancing background knowledge in Culture and Art is an urgent problem of the professional education of a translator/ interpreter. The article deals with the formation of background knowledge of the future translators/ interpreters in Culture and Art in the context of integration of Culture Study and Linguistics courses. The authors show the role of the integrative approach in the process, introduce an original and already tested strategic approach to the formation of the background knowledge of future linguists, allowing to fruitfully integrate linguistic and cultural knowledge as well integrative competences in the university training of future translators/ interpreters. The original definition of the concept, the structure of background knowledge in Culture and Art is revealed, the dominants of background linguocultural knowledge are identified, contributing to comprehension of mentality, system of values and characteristics of the cultural world of the target country and language, ensuring the enculturation and socialization of the translator/ interpreter’s personality.